When does a speech and language therapist investigate ‘influence’? Experiment as a method in research on speech and language disorders - Wolańska, Ewa; Wolański, Adam (Papers in Linguistics, 2024)
Experiment is one of the fundamental methods in scientific research. It is characterized by a different relationship between the researcher and the researched phenomenon than in observation. During observation, the phenomenon under study remains unchanged. Meanwhile, experiment involves actively modifying the phenomenon which is studied. This enables the understanding of causal relationships (i.e. influence) between components or conditions of the phenomenon under study. Scrutinising influence is becoming increasingly popular in various analyses of speech and language disorders. This article presents the experimental method specifically in the context of speech therapy research.